Soil Microbial Respiration and Carbon Turnover under Perennial and Annual Biofuel Crops in two Agricultural Soils - Szymanski, Laura (My University, 2015)
Bioenergy crops have the potential to provide a low carbon-intensive alternative to fossil fuels. More than a century of agricultural research has shown that conventional cropping systems can reduce soil organic matter (SOM) reservoirs, resulting in long-term soil nutrient loss and carbon (C) release to the atmosphere. In the face of climate change and other human disruptions to biogeochemical cycles, identifying biofuel crops that can maintain or enhance soil resources is desirable for the sustainable production of bioenergy. The objective of my research was to compare the effects of four biofuel crop treatments on SOM dynamics in two agricultural soils: Mollisols at Arlington Agricultural Research Station (ARL) in Wisconsin and Alfisols at Kellogg Biological Station (KBS) in Michigan, USA. I used fresh soils collected in 2013 and archived soils collected in 2008 to measure differences among biofuel crops after 5 years of management. Archived soils collected at the time of field treatment establishment provide the opportunity to understand the effects of agricultural management on soil C dynamics over time. Using a one-year-long laboratory soil incubation coupled with a regression model, I separated soils into three SOM pools and their corresponding turnover times. I found that the total amount of soil C respiration in surface soils differed among biofuel crop types and was positively correlated with root biomass. Total soil C respiration increased in the following order: mixed species perennials > monoculture perennials > monoculture annuals. The distribution of C among SOM fractions varied between the two soil types, with greater C content associated with the active fraction in the coarser textured-Alfisol and greater C content associated with the slow-cycling fraction in the Mollisols with high clay content. The active pool (Ca), or biologically available C, was more sensitive to cropping treatment in soils with higher clay content and decreased at both sites from 2008 to 2013. Changes in the Cs, which is theorized to represent SOM that is not rapidly mineralized by microbes, most likely because of occlusion within soil aggregates or absorption to soil particles, indicated an opposite trend, with greater sensitivity in soils with greater sand content. From 2008 to 2013 the change in the Cs among biofuel crops differed, with gains in the Cs in the native prairie and poplar soils and losses in the Cs in the switchgrass and corn soils. Differences in the response of soil C pools to biofuel treatments between our sites suggest that the C sequestration potential of bioenergy crops may differ depending on what crops are grown and on what soil type. Bioenergy crop land-use change affects soil C dynamics, with implications for assessing C costs associated with biofuel production. Monitoring bioavailable C pools may provide an earlier indicator of change in response to agricultural management than bulk soil C stocks.
Includes table of contents, equations, tables, figures, appendices, bibliography
Keywords: Carbon; Bioenergy; Agriculture; Biofuel crops; Microbial respiration; Soil